2016
DOI: 10.1521/aeap.2016.28.2.103
|View full text |Cite
|
Sign up to set email alerts
|

“Inside These Fences Is Our Own Little World”: Prison-Based HIV Testing and HIV-Related Stigma Among Incarcerated Men and Women

Abstract: Correctional facilities offer opportunities to provide comprehensive HIV services including education, testing, treatment, and coordination of post-release care. However, these services may be undermined by unaddressed HIV stigma. As part of a prison-based HIV testing study, we interviewed 76 incarcerated men and women from the North Carolina State prison system. The sample was 72% men, median age 31.5 years (range: 19 to 60). Thematic analysis revealed high levels of HIV-related fear and stigma, homophobia, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…Confidentiality was a key resource for opt-out testing programmes, as the enclosed environment of prison amplifies fear of infectious disease amongst prisoners and staff [51, 57, 58]. BBVs are stigmatised within the prison context (C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Confidentiality was a key resource for opt-out testing programmes, as the enclosed environment of prison amplifies fear of infectious disease amongst prisoners and staff [51, 57, 58]. BBVs are stigmatised within the prison context (C).…”
Section: Resultsmentioning
confidence: 99%
“…Possibly yeah?” (prison officer) [51]. Breaches in auditory and visual confidentiality can also occur when conducting testing, as a result of the confined environment, security requirements, and the increasing reliance on prisoners for the maintenance of the prison environment [39, 47, 51, 5761].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies failed to link HIV stigma to test acceptance, but showed a relation between test acceptance and HIV knowledge [ 13 ]. Thus enhancing the knowledge on HIV risk factors, treatment and prognosis may help to enlarge the proportion of persons willing to be tested [ 14 ]. In French facilities, health care is entrusted to the nearest public hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, patients frequently describe custody as a hostile environment, with concerns about confidentiality and lack of friendly support. As elsewhere, HIV-related stigma segregation are common [34]. Furthermore, newly diagnosed persons may be reluctant to consult an unknown ambulatory unit after release.…”
Section: Factors Associated With Return To Hiv Carementioning
confidence: 97%